Manuel Freire Castrillón and "El Censor"’s “Carta de Galicia” (1786) - Mariño Paz, Ramón; Suárez Vázquez, Damián (Madrygal. Revista de Estudios Gallegos, 2017)
In this paper we defend that Manuel Freire Castrillón was the author of this “Carta de Galicia” and of some other texts that were written in Galician or in a Spanish-Galician interlect (castrapo); we think that one of them could be the poem Un labrador que foy sarxento á os soldados do nobo alistamento (ca. 1808). The arguments we adduce to defend these hypotheses are of biographical, ideological and, most of all, linguistic nature. Finally, we offer a transcription of this letter and some notes of historical and linguistic nature.
Keywords: Manuel Freire Castrillón; Spanish-Galician interlect (castrapo); 18th century; El Censor.